2013
DOI: 10.1073/pnas.1314770110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of vibrational energy dissipation of free OH groups at the air–water interface

Abstract: Interfaces of liquid water play a critical role in a wide variety of processes that occur in biology, a variety of technologies, and the environment. Many macroscopic observations clarify that the properties of liquid water interfaces significantly differ from those of the bulk liquid. In addition to interfacial molecular structure, knowledge of the rates and mechanisms of the relaxation of excess vibrational energy is indispensable to fully understand physical and chemical processes of water and aqueous solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
104
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(125 citation statements)
references
References 51 publications
14
104
2
5
Order By: Relevance
“…3(b)), done to attenuate the spectral contributions from water heating without the need of performing a baseline correction. The result clearly shows the presence of two positive bands at 3648 and 3623 cm −1 and an about twice as intense negative band at 3634 cm −1 , indicating that both a positive (at ∼3648 cm −1 ) and the negative band (at ∼3634 cm −1 ) are sensitive to 18 O labeling of water. In an alternative procedure, the broad spectral contributions of water heating was digitally removed from the lightinduced IR difference spectrum of CaChR1 as described in Sec.…”
Section: Dangling O-h Vibrations Of Active Water Moleculesmentioning
confidence: 95%
See 2 more Smart Citations
“…3(b)), done to attenuate the spectral contributions from water heating without the need of performing a baseline correction. The result clearly shows the presence of two positive bands at 3648 and 3623 cm −1 and an about twice as intense negative band at 3634 cm −1 , indicating that both a positive (at ∼3648 cm −1 ) and the negative band (at ∼3634 cm −1 ) are sensitive to 18 O labeling of water. In an alternative procedure, the broad spectral contributions of water heating was digitally removed from the lightinduced IR difference spectrum of CaChR1 as described in Sec.…”
Section: Dangling O-h Vibrations Of Active Water Moleculesmentioning
confidence: 95%
“…16 In fact, vibrational sum-frequency spectroscopy, a surface-sensitive technique, has shown that the interface is particularly enriched in dangling O-H groups with a characteristic vibration at ∼3680 cm −1 . 17,18 This band is relatively narrow (∼30 cm −1 ) 17,18 with a line width partially limited by the fast reformation of H-bonds at the interface due to fast reorientation of interface water molecules. 18 Dangling O-D groups at the water-air interface oscillate at ∼2740 cm −1 and exhibit narrow bandwidths (11-14 cm −1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Falls eine freie OH-Gruppe H-Brücken bildet, verändert sich ihre Schwingungsfrequenz, jedoch wird die Anregung anfangs noch auf dieser OH-Gruppe verbleiben. Solche Experimente [93] enthüllten in der Tat, dass ein Austausch zwischen den beiden Untergruppen auf einer Zeitskala von ca. 1pss tattfindet, was mit der angenommenen Reorientierungsdynamik übereinstimmt.…”
Section: Bonn Et Alunclassified
“…[23,110] Daraus folgt, dass die Bildung einer Wasserstoffbrücke ein Wegf reier OH-Gruppen ist, schnell Energie abzugeben. Eine andere Mçglichkeit, welche auf vergleichbaren Zeitskalen stattfindet, ist ein beinahe resonanter Energietransfer von der freien OH-Gruppe zur anderen OH-Gruppe desselben Moleküls.B eide Relaxationsmechanismen -R eorientierung und Energietransfer -e rlauben es der freien OH-Gruppe,ü berschüssige Energie auf einer Zeitskala im Subpikosekundenbereich abzugeben, [93] was einige Grçßenordnungen schneller ist als beispielsweise für die nicht-H-gebundenen OH-Gruppen an einer Siliciumdioxidoberfläche. [11] Damit ermçglicht dieser Mechanismus der Wasseroberfläche die hocheffiziente Abgabe überschüs-siger Schwingungsenergie.…”
Section: Bonn Et Alunclassified